5-Carbohydrazide and 5-carbonylazide of pyrazolo[3, 4-b]pyridines as reactive intermediates in the synthesis of various heterocyclic derivatives. Issue 7 (July 2019) - Aly, Ashraf A; El-Emary, Talaat I; Mourad, Aboul-Fetouh E; Khallaf Alyan, Zainab; Bräse, Stefan; Nieger, Martin
5-Carbohydrazides and 5-carbonylazides of pyrazolo[3, 4- b ]pyridines are used to synthesize new heterocyclic derivatives. Some unexpected behaviors are observed in the reactions of the above two species. The structures of the obtained compounds are proved by spectroscopic studies together with elemental and X-ray structure analyses.